KETERIKATAN LAJU PERTUMBUHAN MASYARAKAT, TINGKAT TINGKAT PENGANGGURAN DAN INDEKS PEMBANGUNAN MANUSIA PADA KEMISKINAN DI INDONESIA - NurAziza, Wa Ode (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the influence of population growth, the formal unemployment rate (TPT), and the Human Development Index (HDI) on poverty levels in Indonesia in 2025. Using a quantitative associative approach, this research employs secondary data from Statistics Indonesia (BPS) covering 38 provinces and analyzes using IBM SPSS, the information was subjected to multivariate linear regression 25. Prior to estimation, classical assumption tests—including normality, multicollinearity, and heteroskedasticity tests—were conducted and confirmed that the regression model met all analytical requirements. The results show that population growth and the open unemployment rate have no substantial impact onpoverty, while the The Human Development Index has a negative and substantial impact,indicating that improvements in education, health, and purchasing power directly contribute to reducing poverty levels. Simultaneously, the three variables significantly influence poverty, with an R-square value of 0.688, explaining 68.8% of the variation in poverty across provinces. These findings underscore the pivotal role of human development in poverty reduction, highlighting that structural improvements in education and health yield more substantial impacts than demographic or labor market fluctuations alone. The study provides empirical evidence for policymakers to prioritize human capital investment as a long-term strategy for sustainable poverty alleviation, while also reinforcing theoretical perspectives that frame poverty as a multidimensional phenomenon influenced by more than just economi and social contexts.